An annotated catalogue of the Iranian Galerucinae sensu stricto (Coleoptera: Chrysomelidae) with taxonomic remarks. (2nd January 2021) - Ghahari, Hassan; Beenen, Ron
ABSTRACT: An annotated catalogue for the Iranian Galerucinae s. str. (Coleoptera: Chrysomelidae) is proposed. Based upon literature review and examination of collected material, a total of 56 species in 18 genera are listed for the fauna of Iran. Some species are represented in Iran with more than one subspecies, bringing the total number of taxa to 59. Farsogaleruca Lopatin, 1981 is proposed as new synonym of Radymna Reitter, 1913. The following new combinations are proposed: Radymna insperabilis (Lopatin, 1981) (comb. nov .) and Radymna rufina (Lopatin, 1981) (comb. nov .). The following new synonyms are established: Galerucella medvedevi Beenen, (2008) = Galerucella rishwani Makhan, 2012 syn. nov .; Radymna insperabilis (Lopatin, 1981) (comb. nov .) = Radymna latifrons Beenen, 2014 (syn. nov .). Four species, Calomicrus lividus (Joannis, 1865), Lochmaea caprea (Linnaeus, 1758), Luperus floralis Faldermann, 1837 and Euluperus nairicus (Lopatin, 1990) and one subspecies, Galeruca spectabilis spectabilis (Faldermann, 1837) are recorded from Iran for the first time. Two species have been excluded from the fauna of Iran: Diorhabda elongata (Brullé, 1836) and Luperus flavipennis .